2022
DOI: 10.3389/fimmu.2022.793982
|View full text |Cite
|
Sign up to set email alerts
|

Functional Profile of CD8+ T-Cells in Response to HLA-A*02:01-Restricted Mutated Epitopes Derived from the Gag Protein of Circulating HIV-1 Strains from Medellín, Colombia

Abstract: CD8+ T-cells play a crucial role in the control of HIV replication. HIV-specific CD8+ T-cell responses rapidly expand since the acute phase of the infection, and it has been observed that HIV controllers harbor CD8+ T-cells with potent anti-HIV capacity. The development of CD8+ T-cell-based vaccine against HIV-1 has focused on searching for immunodominant epitopes. However, the strong immune pressure of CD8+ T-cells causes the selection of viral variants with mutations in immunodominant epitopes. Since HIV-1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 64 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Multiple studies have demonstrated the critical role of CD8 + T-cells in controlling HIV-1 replication [ [28] , [29] , [30] ], attributing the control of viremia and slower progression of HIV-1 infection to CD8 + T-cell responses targeting peptides derived from HIV-1 Gag. Previously, we determined the CD8 + T-cell response to Gag peptides restricted to the HLA-A*02 allele and could associate the peptide binding affinity with CD8 + T-cells polyfunctionality [ 22 ]. Importantly, HLA-I allotype restriction is a limitation for developing effective peptide-based vaccines; therefore, identifying immunodominant Gag peptides restricted to the most prevalent HLA-I molecules makes peptide-based vaccines accessible to larger patient cohorts [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple studies have demonstrated the critical role of CD8 + T-cells in controlling HIV-1 replication [ [28] , [29] , [30] ], attributing the control of viremia and slower progression of HIV-1 infection to CD8 + T-cell responses targeting peptides derived from HIV-1 Gag. Previously, we determined the CD8 + T-cell response to Gag peptides restricted to the HLA-A*02 allele and could associate the peptide binding affinity with CD8 + T-cells polyfunctionality [ 22 ]. Importantly, HLA-I allotype restriction is a limitation for developing effective peptide-based vaccines; therefore, identifying immunodominant Gag peptides restricted to the most prevalent HLA-I molecules makes peptide-based vaccines accessible to larger patient cohorts [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the binding affinity of peptides to HLA molecules tends to be associated with higher immune responses [ 22 , 57 ], where amino acid substitutions at critical HIV-1 epitope sites can affect antigenic presentation, reducing the binding affinity and weaken the TCR-peptide-HLA complex interaction [ 58 , 59 ]. Previously, Lund and collaborators reported that peptides with proline in P2 and tyrosine in P9 of the peptide could bind to B7 supertype alleles [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations